Piscolabis (‘snack’): etymological proposals, variations and entries - Prieto García-Seco, David (Revista de Filología Románica, 2015)
This article focuses on the study of the word piscolabis. A review of the possible etymological origins put forward in the relevant literature is first presented. This evinces that the difficulties to offer one single (and safe) etymology probably stem from the lack of documents that record the word under study and that date back to the time when it was first used. This historical account also shows that piscolabis has had different variant forms before and after the dictionary of the Spanish Academy (DRAE) established the current one. Finally, the semantic development that the word has undergone is also provided, which allows us to question the suitability of the entry the word has been assigned in the current edition of the DRAE.
Keywords: piscolabis; etymology; variants; meanings.